Analysis of Hydrogen Gas Injection at Various Compositions in an Existing Natural Gas Pipeline - Liu, Jingxuan; Teng, Lin; Liu, Bin; Han, Peng; Li, Weidong (Frontiers in Energy Research, 2021)
The lack of hydrogen (H2) transportation infrastructure restricts the development of the H2 industry. Owing to the high investment of building specific facilities, using existing natural gas (NG) pipelines to transport a blend of H2 and NG (H2NG) is a viable means of transportation and approach for large-scale long-time storage. However, variation in the thermo-physical properties of an H2NG blend will impact the performance of pipeline appliances. To address the gaps in H2 transmission via an NG system in the context of energy consumption, in the present paper, a one-dimensional pipeline model is proposed to predict the blended flow in a real existing pipeline (Shan–Jing I, China). The data of NG components were derived from real gas fields. Furthermore, the influence of H2 fractions on pipeline energy coefficient and the layout of pressurization stations are comprehensively analyzed. In addition, the case of intermediate gas injection is investigated, and the effects of injection positions are studied. This study serves as a useful reference for the design of an H2NG pipeline system.